An introduction to sustainable transportation policy, planning and implementation - Schiller, Preston L (New York Routledge, 2018)
Acknowledgements -- Foreword -- Introduction and overview -- A highly mobile planet and its challenges : automobile dependence, equity and inequity -- Automobile cities, the car culture and alternative possibilities -- History of sustainable and unsustainable transportation : from walking to wheels and back to walking -- Modes, roads and routes : technologies, infrastructure, functions -- Urban, regional and inter-city public transportation : policy, technical, land use and provider aspects -- Urban design for sustainable and active transportation and healthy communities -- Public policy and effective citizen participation for more sustainable transportation : methods and examples -- A new planning paradigm: from integrated planning, policy and mobility management to repair, regeneration and renewal -- Cities on the move : global exemplars of more sustainable transportation -- Conclusion: growing more exemplars.
Includes bibliographical references and index.
Keywords: Transportation--Environmental aspects